2021
DOI: 10.32585/ijelle.v3i1.1502
|View full text |Cite
|
Sign up to set email alerts
|

Politeness Principles In “Persuasion” Movie

Abstract: The aims of this study is finding and describing politeness principle in Persuasion movie adopted from one of famous novels written by Jane Austen.  This research was a descriptive qualitative research. The data of this research were words, phrases and sentences on the dialogues uttered by the characters which generated politeness principle. The techniques of collecting data used in this research were documentation and content analysis. The procedure of the research obtained from collecting the data, giving co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…After examining the factors that support the success of this class, it can be concluded that differences in culture and country of origin do not cause significant differences. Understanding someone's cultures will be very beneficial for understanding their communication pattern since speech, time, and social condition are embedded in one's culture (Anggraeni, S., 2021). The strategies chosen by the students in the online class were basically the same each week, albeit with different people.…”
Section: Discussionmentioning
confidence: 99%
“…After examining the factors that support the success of this class, it can be concluded that differences in culture and country of origin do not cause significant differences. Understanding someone's cultures will be very beneficial for understanding their communication pattern since speech, time, and social condition are embedded in one's culture (Anggraeni, S., 2021). The strategies chosen by the students in the online class were basically the same each week, albeit with different people.…”
Section: Discussionmentioning
confidence: 99%